Pengaruh Kompetensi, Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan (Studi Kasus Karyawan Perusahaan Pembiayaan Kota Jambi) - Fathiyah Fathiyah; Masnun Masnun; Saiyid Syekh (J-MAS (Jurnal Manajemen dan Sains), 2022)
The purpose of this study is to see the extent to which competence, motivation and discipline affect employee performance, the analysis unit in this study is employees who work in financing companies in Jambi City, the sample number of 67 respondents, data collection techniques using questionnaires and processed by using multiple linear regression analysis, the results of the study show that there is a positive and significant influence both partially and significantly. Simultaneously from the variables of competence, motivation and discipline to the performance of employees of financing companies in Jambi City.